(untitled) (Research, Society and Development, 2020)
The present study seeks to know how quality management can contribute to the reduction of nonconformity in the furniture industries of Carmo do Cajuru, MG. To reach the proposed objective, it was necessary to know the processes of quality control of the companies; identify the main causes of customer complaints regarding product quality; how these complaints are handled. Aiming to demonstrate the importance of quality tools and programs and how to use them in a correct way helps companies reduce waste, returns and achieve customer satisfaction. In the course of this study, as a methodology, a study was developed of multi-sites in some furniture companies in Carmo do Cajuru, as well as bibliographic material and documentation provided by companies. The results show that, when organizations use quality tools, they can identify the origin of defects and can thus develop actions for continuous improvement of processes and treatment of nonconformities; on the other hand, those who do not use the tools or perform an adequate quality control can not measure these indices. Quality is only achieved when companies use management systems and effectively implement their methods, thus involving all parties. The company A, which, even mapping all the information, still shows a high index of nonconformity, being able to improve them if they use the results found in the decision making.